Keretapi Tanah Melayu express Langkawi: problems and prospects / Zorlela Baharum - Baharum, Zorlela (1989)
On the 5th of April 1988, Keretapi Tanah Melayu introduced a new passenger express service between Kuala Lumpur and Arau in Perlis which is known as EXPRESS LANGKAWI. With the existence of this service it will provide convenience for the users of public transportation to travel to the north of Peninsular Malaysia. Before this, there is no express train service operating in Perlis and Kedah states, except the International Train services which is runned by the Thailand Railway Authority. The route nerwork of Express Langkawi begins at Kuala Lumpur and ends at Arau and there are 5 stops between them which are Ipoh, Taipingj Bukit Mertajam, Sungai Petani and Alor Setar. 5The time taken for the journey from Kuala Lumpur to Arau is eight hours. The users of Express Langkawi can be divided into two types. The first comprised of tourists local and foreign destined for Langkawi Island. The second type comprised of the regular travellers or.business or holiday for those who works in Kuala Lumpur area but have their hometown ,in the north. Therefore the role of Express Langkawi is to access the passengers to the local destination that is within the area from Kuala Lumpur to Arau but it also provide a service for the local and foreign tourists to Langkawi.